The Lack of Government Capacity and Rising Community Networks in Building Resilience During the Covid-19 Pandemic: An Insight from Pekalongan City, Indonesia - Mahsun, Muhammad (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2023)
The Covid-19 pandemic has had a wide impact on various sectors of people’s lives, including socio-economic disruption. In Indonesia, at both local and national government levels, the social protection programs have become a key tool for policymakers to overcome the negative impacts of the Covid-19 pandemic crisis. This study aims to examine how the local authorities and community networks called P2SE (Pekalongan Peduli Sosial Ekonomi or Pekalongan Cares Socio-Economy) in Pekalongan city respond to the socio-economic crisis during the Covid-19 pandemic in order to increase the resilience of urban poor and vulnerable group as well as reducing social inequalities. One way of doing this is through integrated social protection provision involving various communities from local authority, academicians, civil society, businessman and micro small and medium enterprises. This article argues that the community networks-based integrated social protection provision model is an alternative strategy to help state authority in addressing poverty and socio-economic inequality in inclusive and participatory ways. In this way, some issues of inequality and political interests in the process of resource distribution related to the provision of social protection can be minimized. Therefore, this model of providing social protection based on integrated community networks can be used as an alternative strategy to reduce inequality and build the resilience of urban poor and other vulnerable groups when facing crisis due to unpredictable disasters such as the Covid-19.